Le stele votive con dedica a Zeus. Un esempio di interazione culturale in Asia Minore - Zedda, Flavia (O T I V M, 2023)
The focus of this paper is to analyse a religious phaenomenon related to a specific area in Phrygia, located between Kütahya and Afyonkarahisar, during the 2nd and the 3rd centuries AD. This phaenomenon is marked by votive steles dedicated to Zeus, who in this territory is linked to an Hittite god, Tarḫunt, a protector of agricultural fields whose symbol was thunder. Zeus was thus referred to by different epithets and represented with a particular iconography, associated with the depiction of animals, phytomorphic elements and work instruments.